Prevalence and factors associated with frailty in elderly people assisted in primary care (Research, Society and Development, 2022)
This study aims to estimate the prevalence of frailty in the elderly and analyze its association with sociodemographic factors, health conditions and social participation. It is a cross-sectional study with a quantitative, analytical approach, with 214 elderly people. Descriptive and inferential analysis was performed. The Clinical-Functional Vulnerability Index-20 was used for data collection and analyzed using descriptive statistics and 5% significance. Among the characteristics of the 214 elderly, 110 (51.4%) were classified as robust, 69 (32.2%) at risk of frailty and 35 (16.4%) frail, associated with more favorable and less favorable health conditions, respectively. . The study evidenced the prevalence of robust elderly, associated with socioeconomic factors and favorable health conditions, while the frail elderly in a situation of social vulnerability, demonstrating the importance of screening and consequent care for its prevention.